2018
DOI: 10.24052/jbrmr/v13is01/art-17
|View full text |Cite
|
Sign up to set email alerts
|

Does the spin-off policy can accelerate the deposit funds in the Indonesian Islamic banking industry?

Abstract: The purpose of this paper is to analyze the impact of spin-off policy that based on Islamic Banking Act No. 21/2008 to the deposit fund growth of Islamic banking industry in Indonesia. This research used panel regression with fixed effect. The variable used in this paper is spin-off variable that used as a dummy variable, and also included the internal factor of industry such as deposit margin, and efficiency ratio (measured by BOPO). Besides the internal element, this research also added the external factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Research findings in the economics discipline revealed that spin-offs positively impacted the market structure of Islamic banks by increasing the number of SBCs (Al Arif et al, 2019) and raising deposit funds (Al Arif, 2018a). On the other hand, spin-offs also had a negative impact in the form of a decrease in market share, performance, and efficiency and an increase in the risk of Islamic banks Trinugroho et al, 2021).…”
Section: Islamic Bank Spin-off Study On Scopus Indexed Journalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research findings in the economics discipline revealed that spin-offs positively impacted the market structure of Islamic banks by increasing the number of SBCs (Al Arif et al, 2019) and raising deposit funds (Al Arif, 2018a). On the other hand, spin-offs also had a negative impact in the form of a decrease in market share, performance, and efficiency and an increase in the risk of Islamic banks Trinugroho et al, 2021).…”
Section: Islamic Bank Spin-off Study On Scopus Indexed Journalsmentioning
confidence: 99%
“…Regarding the growth of deposit funds, spin-off, according to most studies, has been proven to increase the growth of Islamic bank deposit funds (Al Arif, 2014Arif, , 2018bArif, , 2018a). However, one study by Al uncovered that the spin-off had no impact on Islamic bank deposit funds.…”
Section: Spin-off and Performance/efficiency Of Islamic Banksmentioning
confidence: 99%
“…In addition, several studies recommend evaluating the spin-off policy mandated by the Act. Some of the reasons that arise are the difficulty of sharia business units to meet the minimum spin-off requirements [2] and the inconsistency of findings from investigations on several financial ratios [6][7][8][9][10][11][12][13][14][15][16]. Based on the above conditions, this study aims to review the empirical findings of previous studies on the impact of spin-off decisions on the financial performance of Islamic banks.…”
Section: Introductionmentioning
confidence: 99%
“…(Arif M. N., 2014) states that the separation policy must be evaluated because it causes the performance of the banking industry to be less efficient when compared to the conditions before the separation. Various previous studies have discussed a lot about the health of banks before and after spin-off which is assessed in terms of financing, capital, and also the income side such as an empirical study conducted by (Arif M. N., 2018) using panel data regression with the Fixed Effect Model finding that policy The spin-off has a good influence on the growth of deposit funds in the Islamic banking industry in Indonesia. The implication in the results of this study is that the spin-off policy has a good impact on the growth of deposit funds in the Indonesian Islamic banking industry and the spin-off decision is one of the business strategies of Islamic banks and not the goal of the Islamic banking industry.…”
Section: Introductionmentioning
confidence: 99%